Influence of calcium propionate on starter pig performance - D E Real; J C Woodworth; M J Webster; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
A 24-d growth study was conducted to evaluate the effects of low rates of a dietary acidifier, calcium propionate, on weanling pig growth performance. Experimental diets, fed from d 0 to 10, were a control diet with no acidifier, the control diet with 4 lb/ton of Kemgest, or the control diet with 4 or 8 lb/ton calcium propionate. From d 10 to 24, pigs were fed a common phase II diet containing no acidifier. Adding a low rate of acidifier to the diet had no influence on pig performance.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Acidifiers; Nursery pigs; Calcium propionate